Analisis Praktik Tata Kelola Organisasi Publik Dalam Pengelolaan Bumdes Hendrosari Edu Wisata Lontar Sewu - Romadhoni, Diva Octaviona Nur; Khumayroh, Wiwin; Hidayat, Hanan Titis (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
This study aims to analyze the organizational governance of the Hendrosari Edu Wisata Lontar Sewu Village-Owned Enterprise (BUMDes) in Hendrosari Village, Gresik Regency, using the agile governance perspective. The study is motivated by the importance of organizational governance in supporting the success of BUMDes as a village economic institution, as well as a decline in the number of tourists, which indicates the need to strengthen organizational management. The method used is qualitative research with a descriptive approach. Data were obtained through interviews, observations, and documentation of the BUMDes Director, BUMDes Advisors, and the Head of the Tourism Business Unit. The research findings indicate that BUMDes have implemented the six principles of agile governance: good enough governance, business driven, human focused, based on quick wins, systematic and adaptive approach, and simple design and continuous refinement. The application of these principles is evident in the managers’ ability to adapt policies to on-the-ground conditions, develop businesses focused on improving community welfare, encourage resident participation, create early successes that impact the village economy, and engage in continuous innovation and evaluation. Nevertheless, BUMDes management still faces challenges such as a decline in tourist numbers, limited innovation, and suboptimal community participation. Therefore, strengthening strategies for innovation, promotion, and community empowerment is necessary to enhance the sustainability and competitiveness of tourism villages. Keyword : BUMDes, organizational governance, Agile Governance, tourism villages, community participation